Elbasan City's Local Geodesic Network Construction Using Gnss Surveys - Eduart Blloshmi; Bilbil Nurçe (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
This abstract describes how the city of Elbasan's local geodetic support network is being built using GNSS measurements, which will have a favorable effect on the city's economic and social development. The acquired information will be used as a fundamental point of reference for all geodetic projects, as well as for engineering, urban, and scientific designs, as well as geological and geographical studies. In order to determine the three-dimensional position of the points in the official KRGJSH frame—which is based on the ETRF2000 reference frame of reference to the European continental coordinate system ETRS89—as well as the official frame KRGJSH (Albanian Geodetic Reference Framework), in which all the coordinates—it will be necessary to build the local geodetic support network and implement GNSS (Global Navigation Satellite System) measurements.